A Novel Ti–6Al–4V–xSi Coating with Superior Wear and Oxidation Behavior. Issue 10 (12th September 2021) - Liu, Shaopeng; Tang, Yongbai; Xia, Jing; Zhang, Bing; Chen, Yungui
Abstract : Via adding a certain amount of Si on the surface of the Ti–6Al–4V alloy, a novel Ti–6Al–4V– x Si coating is prepared by powder metallurgy method. The results show that an 80 μm thick transition layer is formed between the Ti–6Al–4V– x Si coating and the matrix, and the addition of Si reduces the thickness of α lamellae. Numerous nanosized Ti5 Si3 particles can be detected on the interface of the α/β phase, with a size of about 100 nm and approximately spherical. The main wear mechanisms are adhesive wear and abrasive wear, the average friction coefficients, and mass loss of the sample, as well as the width, depth, and area of wear tracks, decrease with the addition of Si. This is because the dispersed Ti5 Si3 particles can effectively improve the plastic deformation resistance, cutting resistance, adhesion resistance, and crack propagation resistance of the Ti–6Al–4V– x Si coating. The thermal expansion coefficient of Ti5 Si3 is close to that of rutile‐TiO2 and Al2 O3, which reduces the internal stress between the oxide film and the Ti–6Al–4V– x Si coating, and ultimately reduces the cracking tendency of the oxide film. Therefore, the preparation of Ti–6Al–4V– x Si coating can significantly improve the wear resistance and oxidation resistance of Ti–6Al–4V alloy. Abstract : A novel Ti–6Al–4V– x Si coating is prepared by adding a certain amount of Si to the surface of Ti–6Al–4V alloy. The results show that the addition of Si decreases the average friction coefficients, the width, depth, and area of wear tracks, and the cracking tendency of oxide film, which significantly improves the wear resistance and oxidation resistance of Ti–6Al–4V alloy.